Dictyanthus reflexiflorus (Apocynaceae: Asclepiadoideae) a new species from Mexico - Lozada-Pérez, Lucio; Cortez, Ericka B.; Perez-Garcia, Maria De La Luz; González, César Ramiro Martínez; Martínez-Ambriz, Emmanuel (Phytotaxa, 2025)
A new species of Dictyanthus from the state of Michoacan, Mexico, is described and illustrated Dictyanthus reflexiflorus sp. nov. It grows in tropical deciduous forests located in the municipality of Tacámbaro. A phylogenetic analysis based on molecular data (plastid regions trnL-trnF and rps 16) was conducted to explore the relationship of the new species. Results place the new species in Dictyanthus. The morphological characters that support this relationship are the presence of uncinate hairs and a reticulate corolla. The species has unique characteristics within the genus, such as a reflexed corolla and the tube 10-lobed closely pressed to the side of the gynostegium. A key to distinguish Dictyanthus reflexiflorus from congeners in Mexico is included.